Gorontalo Economy Linkage in Perspective Tables IO and IRIO Year 2016 - Sandra Logaritma; Mirta Dwi Wulandari (Gorontalo Development Review, 2022)
Gorontalo Province has the potential to develop, but still has several problems related to inequality and population welfare, so appropriate policies are needed to encourage accelerated development. This study aims to determine the inter-sectoral and inter-regional linkages in Gorontalo Province using the Input Output (IO) and Inter Regional Input Output (IRIO) Tables 2016. The results of this study show that the economy of Gorontalo Province cannot be separated from other provinces and abroad. Gorontalo's leading industries are the supply of electricity and gas (D) and the processing industry (C). Other industries that can be developed are Agriculture, Forestry and Fisheries (A), Trade (G), and Construction (F) which have the largest contribution to the economy of Gorontalo Province. The provinces most affected if there is a change in final demand in Gorontalo Province are DKI Jakarta, Central Java, and East Java. Meanwhile, the provinces that have the greatest impact on Gorontalo Province if there is a change in final demand are North Sulawesi, Central Sulawesi, and Banten.